Seasonal distribution of psychiatric births in England. - Giulio Disanto; Julia M Morahan; Melanie V Lacey; Gabriele C DeLuca; Gavin Giovannoni; George C Ebers; Sreeram V Ramagopalan (PLoS ONE)
There is general consensus that season of birth influences the risk of developing psychiatric conditions later in life. We aimed to investigate whether the risk of schizophrenia (SC), bipolar affective disorder (BAD) and recurrent depressive disorder (RDD) is influenced by month of birth in England to a similar extent as other countries using the largest cohort of English patients collected to date (n = 57,971). When cases were compared to the general English population (n = 29,183,034) all diseases showed a seasonal distribution of births (SC p = 2.48E-05; BAD p = 0.019; RDD p = 0.015). This data has implications for future strategies of disease prevention.